Chemical constituents from methanolic extract of Solanum procumbens Lour (Solanaceae) - Thi Thanh Thuy Tran; Hoang Phu Dang; Trung Nhan Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
Solanum procumbens L. (Solanaceae) were extracted respectively with n-hexane, ethyl acetate, and methanol to obtain the corresponding extracts. The methanolsoluble extract was acidified by adding HCl 0.5 M; this was followed by liquid-liquid partition with CHCl3 to afford CHCl3-soluble fraction. From this fraction, four compounds were isolated and identified as ergosterol peroxide (1), 9,11-dehydroergosterol peroxide (2), N-(N-benzoyl-L-phenylalanyl)-L-phenylalanol (3), and moupinamide (4). Their structures were elucidated based on the NMR spectroscopic analysis and comparison with the literature. All isolated compounds were first reported from S. procumbens.